Impacts of sarA and agr in Staphylococcus aureus Strain Newman on Fibronectin-Binding Protein A Gene Expression and Fibronectin Adherence Capacity In Vitro and in Experimental Infective Endocarditis - Xiong, Yan-Qiong (American Society for Microbiology (ASM), 2004)
We investigated the impacts of sarA and agr on fnbA expression and fibronectin-binding capacity in Staphylococcus aureus in vitro and in experimental endocarditis. Although sarA up-regulated and agr down-regulated both fnbA expression and fibronectin binding in vitro and in vivo, fnbA expression was positively regulated in the absence of both global regulators. Thus, additional regulatory loci contribute to fnbA regulation and fibronectin-binding capacities in S. aureus.